Indikator Kelayakhunian pada Interior Micro-apartment di Jakarta dan Bandung - Mahardhika, Woro Medha; Wibisono, Andriyanto (Serat Rupa: Journal of Design, 2023)
Currently, young families who live in major cities in Indonesia are experiencing a crisis of affordable housing due to limited land, high property prices and changes in the cultural values of urban communities. One of the efforts to deal with the crisis of affordable housing is to build limited-sized dwellings or micro-units, both landed houses and vertical housing. In big cities like Jakarta and Bandung, vertical housing or micro-apartments are an affordable option for young families. However, the limited size of the micro-unit is quite a debate because it is considered inadequate. Therefore, the aspect of liveability has an important role in micro-units. There have been several studies related to the liveability of micro-units. However, there is no research that examines micro-apartments specifically occupied by young families with a child in Jakarta and Bandung. The benefits of this research are knowing the interior factors that influence liveability also the responses and preferences of young families towards micro-units. This study aims to identify the interior factors that can be improved in the micro-apartments occupied by young families with a child in Jakarta and Bandung. The result of this research are expected to become a reference to optimized existing micro-apartments and developing new micro-units in Indonesia. This research is a quantitative descriptive study using survey methods in the form of questionnaires and typological analysis. Study results revealed that 60% of the respondents are satisfied with the living space size but still wanted some improvements. Space layout and furniture are the interior elements that needed to be optimized in micro housing. In addition, although color has a low priority for improvement, color has an important role in the formation of a space ambience, so it needs to be studied further.